(Mis)managing overstock in luxury: Burning inventory and brand trust to the ground. Issue 6 (27th September 2021) - Lee Park, Camila; Fracarolli Nunes, Mauro; Paiva, Ely Laureano
Abstract: Traditionally associated with demands for superior quality and social status, luxury consumption is expected to undergo important transformations in the coming decades. Following a series of societal changes, the environmental impacts generated by companies have become decisive factors in purchasing decisions. Authors have also been stressing the effect of sustainability performance on assorted dimensions of B2C relationships, thereby putting pressure on companies to incorporate these trends. While luxury brands have sought to adapt their business models, a series of unsustainable practices continue to be part of their day‐to‐day operations. Among the most controversial is the burning of unsold products as a way of preserving brand value. In addition to attracting unwanted attention from the media, the destruction of fully functional products often triggers harsh reactions from environmentalists, as well as from consumers who are more sensitive to these issues. The prospect of growing demands for environmental responsibility, coupled with the perception that any failure in this regard represents a risk to the reputational assets of luxury companies, makes the investigation of inventory burning in relation to stakeholders' perceptions an urgent task. Aiming to offer new insights into the future of sustainable luxury consumption, we assess the impact of this practice on two key components of consumer perception. Through two scenario‐based experiments with a total sample of 492 participants, we investigate the effects of inventory burning on consumer trust and avoidance of luxury brands. Our results indicate the need for luxury brands to further incorporate environmental demands as they seek to serve increasingly demanding eco‐conscious consumers.